C2AIDER: cognitive cloud exoskeleton system and its applications. Issue 2 (16th May 2019) - Wang, Yilin; Cheng, Hong; Hou, Lei
Abstract : Lower extremity exoskeleton systems have been widely applied in walking assistance, rehabilitation, and augmentation‐related applications merely through human‐exoskeleton movement collaboration, which cannot analyse cognitive load and pressure of pilots. Cognitive exoskeleton systems can reinforce cognitive cooperation of the human‐exoskeleton systems through perception and assessment. Cognitive cloud exoskeleton systems can enhance the ability of the continuous learning and transfer learning of the exoskeleton systems through cloud brain platform. This paper presents a cognitive cloud exoskeleton system Cognitive Cloud AssItive DEvice for paralysed patient ( c 2 AIDER ). The main idea is that the cooperation between the c 2 AIDER system and pilots is more intelligent and natural through cloud brain platform, which can achieve high‐performance computing thus providing better walking assistance for pilots.